Development of a complex intervention to support parents of adolescents with chronic illness transferring from pediatrics to adult care (ParTNerSTEPs) - Ena Lindhart Thomsen; Bente Appel Esbensen; Signe Hanghøj; Helena Hansson; Kirsten Arntz Boisen (BMC, 2022)
Abstract Background Transition from pediatric to adult care for adolescents with chronic illness is associated with outpatient non-attendance and low treatment adherence in adolescents, and with anxiety and concerns among parents. Recent studies have shown that parent involvement results in better transitions. The aim of this paper was to describe the development, through participatory design, of a comprehensive transfer program targeted to parents of adolescents with chronic illness. Methods The study was based on the UK Medical Research Council's (MRC) framework on developing and testing complex interventions. To increase the program's feasibility and relevance, participatory design was chosen as the overall method. A collaboration group of parents, young people and health care professionals (HCP) were actively involved in the development of the program. The program was developed in three development stages, in accordance with the MRC framework: 1) identifying the evidence base, 2) identifying theory, and 3) modelling process and outcomes. Results Together with the collaboration group, we developed a comprehensive transfer program targeting parents, by undertaking an iterative process, involving a literature review, individual interviews, workshops and online brainstorms. The program, called ParTNerSTEPs (Parents in Transition - a Nurse-led Support and Transfer Educational Program) comprised three components: 1) an informative website, 2) online educational events for parents, and 3) transfer consultations with providers from both pediatrics and adult care. Conclusions The MRC framework was successfully applied to develop a comprehensive transfer program targeting parents of adolescents with chronic ilness. By incorporating the principles of participatory design in the development phase, we ensured that both parents' and adolescents' needs were represented and addressed in the program. Trial registration ClinicalTrials.gov ID NCT04969328.